Declining free thyroxine levels over time in irradiated childhood brain tumor survivors. Issue 12 (December 2018) - van Iersel, Laura; Clement, Sarah C; Schouten-van Meeteren, Antoinette Y N; Boot, Annemieke M; Claahsen-van der Grinten, Hedi L; Granzen, Bernd; Sen Han, K; Janssens, Geert O; Michiels, Erna M; van Trotsenburg, A S Paul; Vandertop, W Peter; van Vuurden, Dannis G; et al.
Abstract : Objective: The incidence of cranial radiotherapy (cRT)–induced central hypothyroidism (TSHD) in childhood brain tumor survivors (CBTS) is reported to be low. However, TSHD may be more frequent than currently suspected, as its diagnosis is challenging due to broad reference ranges for free thyroxine (FT4) concentrations. TSHD is more likely to be present when FT4 levels progressively decline over time. Therefore, we determined the incidence and latency time of TSHD and changes of FT4 levels over time in irradiated CBTS. Design: Nationwide, 10-year retrospective study of irradiated CBTS. Methods: TSHD was defined as 'diagnosed' when FT4 concentrations were below the reference range with low, normal or mildly elevated thyrotropin levels, and as 'presumed' when FT4 declined ≥ 20% within the reference range. Longitudinal FT4 concentrations over time were determined in growth hormone deficient (GHD) CBTS with and without diagnosed TSHD from cRT to last follow-up (paired t -test). Results: Of 207 included CBTS, the 5-year cumulative incidence of diagnosed TSHD was 20.3%, which occurred in 50% (25/50) of CBTS with GHD by 3.4 years (range, 0.9–9.7) after cRT. Presumed TSHD was present in 20 additional CBTS. The median FT4 decline in GH-deficient CBTS was 41.3% ( P < 0.01) to diagnosis of TSHD and 12.4% ( P = 0.02) in GH-deficient CBTS without diagnosed TSHD. Conclusions: FT4 concentrations in CBTS significantly decline over time after cRT, also in those not diagnosed with TSHD, suggesting that TSHD occurs more frequently and earlier than currently reported. The clinical relevance of cRT-induced FT4 decline over time should be investigated in future studies.